Clinical significance of blood supply of the fornix of brain: a cadaveric study - Patcharaporn Srisaikaew,; Tanat Vaniyapong,; Srijit Das,; Pasuk Mahhakranukrauh, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Transient ischemic attack (TIA) of the fornix causes a spectrum of memory deficits, which increases the contributions of vascular disease to dementia which is known as early-onset dementia. As the fornix, the white matter bundle, serves as the major efferent pathway connecting the hippocampus with other human limbic structures, a variety of lesions that damage the fornix could lead to significant memory impairment. Therefore, the blood supply of fornix is a concern. This study aims to study the arterial supply of fornix. Thirty fresh human cadaveric heads were used. They were preserved by the mixture of fixation solution for fornix anatomical dissection and injected with coloured latex solution for visualization of cerebral vasculature through 6 critical steps of approaches. The result showed that the fimbriae of fornix were mainly supplied by the branches of posterior cerebral artery (PCA) and two cases were found to have the anastomoses of those branches with the choroidal artery (ChA). The proposed technique confirmed the ability of coloration of human cerebral vasculature by using colored latex solution which penetrated into cerebral small vessels leading to a precise understanding of the arterial supply of fornix in human brain which is essential for neurosurgeon, neurosurgical training and researchers.